Space-time dynamics of brazilian urban expansion from the use of remote Sensing - a review (Research, Society and Development, 2021)
The use of remote sensing has been a tool of paramount importance for the study of land use and occupation, in Brazil, scientific production with this theme has been presenting increasingly efficient results both in numbers and in the quality of the works, so this study is based on a bibliographic review of remote sensing in Brazilian urban areas, thus having the main objective of this study was to identify the use of remote sensing applied to the study and analysis of urban areas in Brazil, for this we identified the satellites used in the researches; the methods and techniques for the studies of urban areas and list the Brazilian regions that most use remote sensing data for studies of urban areas. For this purpose, we used a research protocol, and articles were used that presented a hierarchical classification of urban land use, for this we searched indexed articles in the period from 1972 to 2020 on three electronic bases: ScienceDirect, the Capes/CAFÉ platform and Google Scholar. This procedure resulted in the amount of 283 results computed in the selected search engines, where 54 (Fifty-five) articles were selected that began to compute the sample for the study in question, as a result by regions the analysis of the sample demonstrates that in quantitative terms the Brazilian regions appear in the following order: Southeast, South, Northeast, Midwest and North, and in both there is the use of remote sensing in urban planning, given the proportionalities of importance depending on the degree of understanding of the importance of this tool by decision makers.